PERAN GURU BK DALAM MEMBANTU PESERTA DIDIK YANG MENGALAMI PERILAKU MENYIMPANG DI SMP NEGERI 2 BAYANG KABUPATEN PESISIR SELATAN - Syaputri, Anisa; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
Based on observations and interviews that researchers do in the field that information obtained: the learners who behave like stray in and out of class at the PBM process takes place, hanging out in the cafeteria and violated school discipline. The purpose of this study was to describe: 1) The role of counselor in preventing deviant behavior of students in Junior High School 2 Bayang Kabupaten Pesisir Selatan. 2) The teachers role in tackling misbehavior BK learners in SMP Negeri 2 Bayang Kabupaten Pesisir Selatan. This research is a descriptive study that systematically describes and actual research about the state of the object. The study population was all students in SMP Negeri 2 Bayang, amounting to 602 people. Techniques used in sampling, is stratified random sampling where the number of samples in each stratum is proportional to the number of members of the population in each class population. So, the total sample of 86 people. The instrument used in this study was a questionnaire while the percentage of data analysis techniques used. Based on the results of the study researchers suggest to teachers BK, in order to provide guidance and counseling services in order to alleviate problems related to student misconduct. Principal participate in support services BK held by BK teachers at school. For guidance counseling courses, as input and suggestions, and to guide future research compiled.